Effects of Megaplasmid Loss on Growth of Neurotoxigenic Clostridium butyricum Strains and Botulinum Neurotoxin Type E Expression - Scalfaro, Concetta; Iacobino, Angelo; Grande, Laura; Morabito, Stefano; Franciosa, Giovanna (Frontiers in Microbiology, 2016)
Clostridium butyricum strains that atypically produce the botulinum neurotoxin type E (BoNT/E) possess a megaplasmid of unknown functions in their genome. In this study, we cured two botulinum neurotoxigenic C. butyricum type E strains of their megaplasmids, and compared the obtained megaplasmid-cured strains to their respective wild-type parental strains. Our results showed that the megaplasmids do not confer beta-lactam resistance on the neurotoxigenic C. butyricum type E strains, although they carry several putative beta-lactamase genes. Instead, we found that the megaplasmids are essential for growth of the neurotoxigenic C. butyricum type E strains at the relatively low temperature of 15°C, and are also relevant for growth of strains under limiting pH and salinity conditions, as well as under favorable environmental conditions. Moreover, the presence of the megaplasmids was associated with increased transcript levels of the gene encoding BoNT/E in the C. butyricum type E strains, indicating that the megaplasmids likely contain transcriptional regulators. However, the levels of BoNT/E in the supernatants of the cured and uncured strains were similar after 24 h and 48 h culture, suggesting that expression of BoNT/E in the C. butyricum type E strains is not ultimately controlled by the megaplasmids. Together, our results reveal that the C. butyricum type E megaplasmids exert pleiotropic effects on the growth of their microbial hosts under optimal and limiting environmental conditions, and also highlight the possibility of original regulatory mechanisms controlling the expression of BoNT/E.